An Error Analysis of Derivational Affixes in Narrative Essay Written by Eleventh Grade Students at Islamic Modern Senior High School - Qolby, Sofiatul; Daril Hanna, Ina; Listyowati , Rini (Institut Agama Islam Negeri Palopo, 2025)
This research aims to analyze errors in the use of derivational affixes in narrative writing by eleventh-grade students at MA Al Djufri Blumbungan Pamekasan. This study uses a mix method approach, combining both qualitative and quantitative methods. Data were collected from 22 student essays, which were analyzed using descriptive qualitative techniques to identify the types of errors, as well as frequency and percentage calculations to determine the most dominant errors. Errors in the use of derivational affixes were categorized into four types: omission, addition, misformation, and misordering. The results of the study show that misformation errors were the most dominant, with a percentage of 68%, followed by omission and addition errors, each at 12%, and misordering errors at only 8%. From this analysis, it can be concluded that the majority of errors occur in derivations that change word classes, particularly in nouns and adjectives. The findings emphasize the importance of strengthening instruction on the use of derivational affixes in writing instruction at the high school level to reduce morphological errors among students.